An Analysis of the Effect of Financial Resource Management on the Financial Well-Being of Generation Z, with Financial Behaviour as a Moderating Variable - Eni Kaharti Eni; Dwi Artati (Amkop Management Accounting Review (AMAR), 2026)
This study aims to analyse the effects of Financial Resources Management and Financial Behaviour on Financial Well-Being and to examine the moderating role of Financial Behaviour among employed members of Generation Z in the Kebumen region. The study employed a quantitative approach with an explanatory design and a cross-sectional survey method. Data were collected through an online questionnaire distributed from January to June 2026 to 200 respondents selected using purposive sampling. The data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The measurement model evaluation showed that all constructs satisfied the criteria for convergent validity, discriminant validity, and reliability. The hypothesis testing results indicated that Financial Resources Management had a positive and statistically significant effect on Financial Well-Being, with a path coefficient of 0.142 and a p-value of 0.036. Financial Behaviour also had a positive and statistically significant effect on Financial Well-Being, with a path coefficient of 0.353 and a p-value of less than 0.001. However, the interaction between Financial Behaviour and Financial Resources Management did not have a statistically significant effect on Financial Well-Being, with a coefficient of 0.018 and a p-value of 0.797. The R² value of 0.169 indicates that the model explained 16.9% of the variance in Financial Well-Being. These findings confirm that Financial Behaviour functions more strongly as a direct predictor than as a moderating variable.